2008
DOI: 10.1182/blood-2007-02-071910
|View full text |Cite
|
Sign up to set email alerts
|

P2Y receptor signaling regulates phenotype and IFN-α secretion of human plasmacytoid dendritic cells

Abstract: Plasmacytoid dendritic cells (PDCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…P2Y 14 receptor transcripts are expressed in several human tissues, including placenta, stomach, intestine, adipose, brain, lung, spleen, heart, and circulating leukocytes (3,(5)(6)(7). UDPsugar-promoted signaling has been reported in astrocytes and microglial cells (8,9), lung epithelial cells (10), bone marrow hematopoietic stem cells (11), and multiple types of peripheral immune cells, including neutrophils, lymphocytes, and dendritic cells (6,7,12,13). These observations suggest that UDPsugars, high energy donor substrates in biosynthetic reactions, potentially are released from cells in a regulated fashion to perform autocrine/paracrine signaling.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…P2Y 14 receptor transcripts are expressed in several human tissues, including placenta, stomach, intestine, adipose, brain, lung, spleen, heart, and circulating leukocytes (3,(5)(6)(7). UDPsugar-promoted signaling has been reported in astrocytes and microglial cells (8,9), lung epithelial cells (10), bone marrow hematopoietic stem cells (11), and multiple types of peripheral immune cells, including neutrophils, lymphocytes, and dendritic cells (6,7,12,13). These observations suggest that UDPsugars, high energy donor substrates in biosynthetic reactions, potentially are released from cells in a regulated fashion to perform autocrine/paracrine signaling.…”
mentioning
confidence: 88%
“…P2Y receptors belong to the superfamily of G protein-coupled receptors. At least eight human P2Y receptor species have been identified, seven of which (P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , P2Y 12 , and P2Y 13 ) are activated by adenine and/or uridine nucleoside di-and triphosphates (2). The P2Y 14 receptor was identified as the eighth member of the P2Y family (3,4).…”
mentioning
confidence: 99%
“…One of such examples is the synergism between both families in the activation of dendritic cells, which is necessary for the efficient initiation of immune responses. In addition to Ag, the presence of P2 agonists coming from necrotic cells results in a synergistic activation and maturation of dendritic cells and, therefore, in a more efficient signaling in T cells, leading to a higher expression of proinflammatory mediators and adhesion molecules (3,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…subject. Recent studies have shown that extracellular nucleotides, such as UDP, can modulate the function and IFN-a production of human pDCs through the P2Y6 receptor, which is mainly expressed on pDCs, not T cells (35,36). Thus, it is likely that the function of uGD-derived DCs is reversed by the P2Y6 ligand.…”
Section: Proportionmentioning
confidence: 99%